Management of the Madrasah Aliyah Curriculum of Religious Sciences Program at MAN 1 Purwakarta - Imam Tabroni; Nashirotun Fitriani Rahmi; Nurpita Sari (Jurnal Multidisiplin Madani, 2022)
This study aims to determine how the curriculum management in MAN 1 PURWAKARTA, namely planning, implementing, and evaluating the curriculum, including obstacles in curriculum management. This study uses a qualitative method with a case study approach. The research subjects consisted of the principal of the madrasa, the deputy head of the madrasa, and the teaching staff. The object of research: learning activities, and school conditions. Collecting data in this study using interviews, observation, and document analysis. The validity of the data is done by testing the credibility, transferability, dependability, and confirmability. Data analysis used Miles-Huberman interactive analysis which consisted of data reduction, data presentation, and drawing conclusions. The results of this study indicate that curriculum planning is planned through workshops that are guided by the national curriculum and the development of local excellence. This evaluation is also carried out in the form of mid-semester assessments, end-of-semester assessments and national exams. The inhibiting factors for managing this curriculum include: program modules that are not standardized and diktat books are not systematic; lack of patience of educators in making learning tools and smooth mastery of computer technology; infrastructure facilities that are still inadequate; student discipline problems in participating in learning; crowded school activities, and organizations reduce the focus of student learning; and language skills of children who have not been able to understand the text as a whole.